Solusi Peningkatan Sumberdaya Manusia Pada Baytul Maal wat Tamwil (BMT) di Indonesia Melalui Pendekatan Analytic Network Process (ANP) - Fiqih Apriadi; Muhammad Findi Alexandi (AL-MUZARA'AH, 2013)
Baitul Maal wat Tamwil (BMT), as a micro financial institution, has a strategic role in Indonsia. The lack in quality of human resources has been a challenge since its establishment. This issue still needs to be considered seriously. Therefore, this study tries to examine the internal problems regarding the BMT human resources in Indonesia. Analytic Network Process (ANP) is used as the methodology to overcome the objective of this study. Survey and indepth interview are conducted to collect the data. The results showed that the main problems occurred in human resource management were when it dealt with training and skill development programs. Moreover, ethics and morality of the employees needs to be improved continuosly as part of the worship to Allah SWT.